Hak Tenurial Masyarakat Adat Dalam Wilayah Kesatuan Pengelolaan Hutan Lindung - Ahmad, Sukmawati; Tjoa, Marthina; iskar, iskar (Universitas Pattimura, 2019)
This study aims to identify community tenure rights in the Ambon City KPHL and find out the factors that influence community tenure rights. The research method used is a case study research with a qualitative approach. Data was collected through interviewing respondents and key informants. The results showed that the types of community tenure rights in the State of Soya in the KPHL management area included ownership rights, land rights, exclusive preference rights to use rights and utilization rights. Whereas the factors that influence community tenure rights include internal factors, namely land leases, rights to trees, land sale and purchase, and original rights. External factors include the establishment of protected areas, the absence of local regulations governing community tenure rights, development of educational institutions, rights to trees and land grabbing.